Synergy Effect in Platform Ecosystem: A Quantitative Analysis of Smart Home Products - Ruiyang Tang; Yuki Inoue; Masaharu Tsujimoto (IEEE Access)
With the platform ecosystem’s development, synergy effects’ importance has grown. This study aims to elucidate synergy effect characteristics within the platform ecosystem and their impact on consumers’ value perception. We collected 405 smart home products from Amazon.co.jp as samples. Synergy effect is categorized into synergy with platform and complements. Firstly, text mining summarizes the characteristics of synergy effect between complements and platform (System-to-system interoperability, Coordinated interconnection integration, User interaction coordination, Remote coordination flexibility) and synergy effect between complements and complements (Dynamic interaction coordination, Multi-scenario coordination, Spatial Controllability, Personalized setting coordination). Then, two models, purchase intention and user experience, explore these characteristics’ impact on consumers’ value perception. The results show that interactions between system-to-system interoperability and multi-scenario coordination, and between coordinated interconnection integration and spatial controllability, positively affect purchase intention. However, interactions between user interaction coordination and spatial controllability, and between user interaction coordination and personalized setting coordination, negatively affect purchase intention. Interactions between user interaction coordination and multi-scenario coordination, between remote coordination flexibility and dynamic interaction coordination, and between remote coordination flexibility and spatial controllability, positively affect user experience. This research provides new perspectives on synergy effect within the platform ecosystem and implications for product development.